Financial Literacy and Personal Financial Management of Students: A Descriptive Analysis - Sandria, Wella; Siswoyo, Siswoyo; Basri, Hasan (Universitas muhammadiyah palembang, 2021)
This research is a quantitative descriptive study based on a survey of research subjects, where the results of the study can provide an accurate picture of the level of financial literacy in students of Management Study Program, Muhammadiyah University of Jambi. This study uses primary data through interviews, observation and distributing questionnaires using google form media to 166 students out of a total of 284 active students registered in the Management Study Program of the Muhammadiyah University of Jambi for the 2019/2020 Academic Year. Secondary data were obtained from publications related to literature and financial decisions. The variable of the respondent's level of financial literacy was measured by 19, while the variable of financial decisions was measured by 8 questions related to basic knowledge of finance, savings and loans, insurance and investment. The results of the analysis of this study found that the level of financial literacy of students of Management Study Program, Muhammadiyah University of Jambi was still in the low and medium category. Low literacy is shown in the insurance and investment aspects, while moderate aspects are shown in the results of basic knowledge, savings and loans. From the results of financial decision analysis based on students' personal opinions, it was also found that a lack of financial literacy made it difficult for them to make financial decisions, especially in the long term.